LBA4Peripheral neuropathy (PN), thrombocytopenia (TCP) and central nervous system (CNS) recurrence: An update of the phase III KATHERINE trial of post-neoadjuvant trastuzumab emtansine (T-DM1) or trastuzumab (H) in patients (pts) with residual invasive HER2-positive breast cancer (BC). (24th November 2019) - Untch, M; Geyer, C E; Huang, C; Loibl, S; Wolmark, N; Mano, M S; von Minckwitz, G; Brufsky, A; Pivot, X; Polikoff, J; Fontana, A; Kaufman, B; et al.
Abstract: Background: We analyzed KATHERINE trial (NCT01772472) data to assess TCP, PN and CNS recurrence, key considerations in anti-HER2 treatment of BC pts. Methods: Pts received 14 cycles of post-neoadjuvant T-DM1 (3.6 mg/kg IV q3w) or H (6 mg/kg IV q3w). Safety (per NCI CTCAE v4.0; all pts receiving ≥1 dose of study drug) and CNS recurrence (intent-to-treat population) were assessed. Results: Baseline (BL) neuropathy was well balanced between arms (T-DM1 22.7%; H 21.4%). In both arms, BL neuropathy was not associated with higher PN incidence (T-DM1 36.3% H 17.5% vs T-DM1 31.1% H 16.8%) however it was associated with longer median PN duration and lower resolution rate (352–337 days [d] 66–64% vs 243–232 d 81–83%). PN incidence was similar, irrespective of prior taxane (docetaxel T-DM1 32%; H 18%; paclitaxel T-DM1 32%; H 17%). In the T-DM1 arm, prior platinum was associated with higher TCP incidence (mostly grade 1–2) (36% vs 27%) while median duration and resolution rate of grade 3–4 TCP were similar regardless of prior platinum (33 d vs 29 d; 95% vs 96%). In the H arm, TCP rate was only 2.4% precluding further analysis. The numerically higher rate of CNS recurrence as first IDFS event for T-DM1 may be explained by competing risk, as observed in H adjuvant trials. T-DM1 was not associated with an increased overall risk of CNS recurrence and there was no evidence of subsequent overall survival (OS) detriment (Table). Conclusions: BL neuropathy may impact duration and resolution of PN with T-DM1 or H, but PN incidence was not affected by BL neuropathy or type of prior taxane. Prior platinum was associated with higher TCP incidence in the T-DM1 arm. The numerical difference in CNS recurrence as first IDFS event for T-DM1 vs H may be explained by competing risk and had no detrimental effect on OS. Clinical trial identification: NCT01772472. Editorial acknowledgement: Ify Sargeant of Twist Medical LLC and funded by F. Hoffmann-La Roche. Legal entity responsible for the study: F. Hoffmann-La Roche. Funding: F. Hoffmann-La Roche. Disclosure: M. Untch: Honoraria (institution), Advisory / Consultancy: AbbVie; Honoraria (institution), Advisory / Consultancy: Amgen; Honoraria (institution), Advisory / Consultancy: AstraZeneca; Honoraria (institution), Advisory / Consultancy: Celgene; Honoraria (institution), Advisory / Consultancy: Daiichi Sankyo; Honoraria (institution), Advisory / Consultancy: Eisai; Honoraria (institution), Advisory / Consultancy: Lilly Germany; Honoraria (institution), Advisory / Consultancy: Lilly International; Honoraria (institution), Advisory / Consultancy: Merck; Honoraria (institution), Advisory / Consultancy: MSD; Honoraria (institution), Advisory / Consultancy: Mundipharma; Honoraria (institution), Advisory / Consultancy: Myriad Genetics; Honoraria (institution), Advisory / Consultancy: Novartis; Honoraria (institution), Advisory / Consultancy: Odonate; Honoraria (institution), Advisory / Consultancy: Pierre Fabre; Honoraria (institution), Advisory / Consultancy: Pfizer; Honoraria (institution), Advisory / Consultancy: PUMA Biotechnology; Honoraria (institution), Advisory / Consultancy: F. Hoffmann-La Roche; Honoraria (institution), Advisory / Consultancy: Sanofi Aventis; Honoraria (institution), Advisory / Consultancy: TEVA Pharmaceuticals. C.E. Geyer, Jr.: Research grant / Funding (institution), Travel / Accommodation / Expenses, Non-remunerated activity/ies: Genentech/Roche; Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Research grant / Funding (institution), Non-remunerated activity/ies: AbbVie; Honoraria (self), Advisory / Consultancy: Celgene. C. Huang: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Amgen; Honoraria (self), Advisory / Consultancy: Eli Lily; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Pfizer; Honoraria (self), Speaker Bureau / Expert testimony: Novartis; Honoraria (self): EirGenix; Honoraria (self): OBI Pharma; Honoraria (self): AstraZeneca; Honoraria (self): MSD; Honoraria (self): Daiichi Sankyo. S. Loibl: Honoraria (institution): Roche; Honoraria (institution): AbbVie; Honoraria (institution): Amgen; Honoraria (institution): AstraZeneca; Honoraria (institution): Celgene; Honoraria (institution): Novartis; Honoraria (institution): Pfizer; Honoraria (institution): Seattle Genentics; Honoraria (institution): Teva; Honoraria (institution): Vifor; Honoraria (institution): PRIME; Honoraria (institution): Daiichi. M.S. Mano: Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: Oncologia Brasil; Honoraria (self), Advisory / Consultancy: AstraZeneca; Shareholder / Stockholder / Stock options: Hypera; Shareholder / Stockholder / Stock options: Fleury; Shareholder / Stockholder / Stock options: Biotoscana. G. von Minckwitz: Research grant / Funding (self): Pfizer; Honoraria (self), Research grant / Funding (self): Amgen; Honoraria (self), Research grant / Funding (self): Roche; Research grant / Funding (self): Celgene; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Myriad Genentics; Research grant / Funding (self): AbbVie; Research grant / Funding (self): Vifor Pharma. A. Brufsky: Advisory / Consultancy: Eisai; Advisory / Consultancy: Myriad Pharmaceuticals; Advisory / Consultancy: Merck; Advisory / Consultancy: Bioarray Therapeutics; Advisory / Consultancy: Puma Biotechnology; Advisory / Consultancy: Genomic Health; Advisory / Consultancy: NanoString Technologies; Advisory / Consultancy: BioTheranostics; Advisory / Consultancy: Lilly; Advisory / Consultancy: Bayer; Advisory / Consultancy: Novartis; Advisory / Consultancy: Celgene; Advisory / Consultancy: Agendia; Advisory / Consultancy: Genentech/Roche; Advisory / Consultancy: Pfizer. B. Kaufman: Honoraria (self), Speaker Bureau / Expert testimony: Roche; Honoraria (self), Speaker Bureau / Expert testimony: Pfizer; Honoraria (self), Advisory / Consultancy: AZ; Honoraria (self), Advisory / Consultancy: Novartis. T. Boulet: Research grant / Funding (institution), Full / Part-time employment: Genentech/Roche. H. Liu: Shareholder / Stockholder / Stock options, Full / Part-time employment: Roche. C. Song: Shareholder / Stockholder / Stock options, Full / Part-time employment: Roche. E.P. Mamounas: Honoraria (self): Genentech/Roche; Honoraria (self): Genomic Health, Inc.; Honoraria (self): Biotheranostics; Honoraria (self): Merck; Honoraria (self): Daiichi Sankyo.